Expression of Recombinant Genes in the Yeast Pichia pastoris. Issue 17 (11th September 2018) - Cregg, James M.; Tolstorukov, Ilya; Kusari, Anasua; Sunga, Anthony Jay; Madden, Knut; Chappell, Thomas
Abstract: The synthesis of specific recombinant proteins using single‐celled organisms from bacteria to mammalian tissue culture cells has become a major source of biopharmaceutical products for the industry and a source of a wide variety of proteins for academic research. A range of organisms are utilized for this purpose. One of the newest and most promising of these is the yeast Pichia pastoris . This article provides detailed basic protocols for the expression of heterologous genes and the synthesis of recombinant proteins utilizing this yeast. Specifically provided are protocols for the insertion of foreign vector DNAs into the yeast by electroporation, amplification of vector sequences by the post‐translational vector amplification (PTVA) method, and growth and expression of foreign genes in shake flask cultures. © 2018 by John Wiley & Sons, Inc.